Identification and Enzymatic Activity Evaluation of a Novel CYP2C9 Allelic Variant Discovered in a Patient - Zhou, Xiao-Yang; Lu, Xiang-Ran; Li, Ying-Hui; Ma, Ya-Qing; Zhao, Shi-Wen; Wang, Fang; Xu, Ren-Ai; Hu, Guo-Xin; Cai, Jian-Ping (Frontiers in Pharmacology, 2021)
Warfarin is a widely prescribed anticoagulant but the doses required to attain the optimum therapeutic effect exhibit dramatic inter-individual variability. Pharmacogenomics-guided warfarin dosing has been recommended to improve safety and effectiveness. We analyzed the cytochrome P450 2C9 (CYP2C9) and vitamin K epoxide reductase complex subunit 1 (VKORC1) genes among 120 patients taking warfarin. A new coding variant was identified by sequencing CYP2C9. The novel A>G mutation at nucleotide position 14277 led to an amino acid substitution of isoleucine with valine at position 213 (I213V). The functional consequence of the variant was subsequently evaluated in vitro. cDNA of the novel variant was constructed by site-directed mutagenesis and the recombinant protein was expressed in vitro using a baculovirus–insect cell expression system. The recombinant protein expression was quantified at apoprotein and holoprotein levels. Its enzymatic activities toward tolbutamide, warfarin and losartan were then assessed. It exhibited lower apparent Km values and increases of 148%, 84% and 67% in the intrinsic clearance of tolbutamide, warfarin and losartan, respectively, compared to wild-type CYP2C9*1, indicating dramatically enhanced in vitro enzymatic activity. Our study suggests that the amino acid at position 213 in wild-type CYP2C9*1 may be important for the enzymatic activity of CYP2C9 toward tolbutamide, warfarin and losartan. In summary, a patient taking high-dose warfarin (6.0 mg/day) in order to achieve the target international normalized ratio was found to have a mutation in the CYP2C9 gene.